The Women of FOCIS: Promoting Equality and Inclusiveness in a Professional Federation of Clinical Immunology Societies - Reed, Elaine F.; Chong, Anita S.; Levings, Megan K.; Mutrie, Caley; Laufer, Terri M.; Roncarolo, Maria Grazia; Sykes, Megan (Frontiers in Immunology, 2022)
The authors of this article, all women who have been deeply committed to the Federation of Clinical Immunology Societies (FOCIS), performed a retrospective analysis of gender equality practices of FOCIS to identify areas for improvement and make recommendations accordingly. Gender data were obtained and analyzed for the period from January 2010 to July 2021. Outcome measures included numbers of men and women across the following categories: membership enrollment, meeting and course faculty and attendees, committee and leadership composition. FOCIS’ past and present leaders, steering committee members, FCE directors, individual members, as well as education, annual meeting scientific program and FCE committee members and management staff of FOCIS were surveyed by email questionnaire for feedback on FOCIS policies and practice with respect to gender equality and inclusion. Although women represent 50% of the membership, they have been underrepresented in all leadership, educational, and committee roles within the FOCIS organization. Surveying FOCIS leadership and membership revealed a growing recognition of disparities in female leadership across all FOCIS missions, leading to significant improvement in multiple areas since 2016. We highlight these changes and propose a number of recommendations that can be used by FOCIS to improve gender equality.